2014
DOI: 10.1177/0300060514531925
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dose of dexmedetomidine for attenuating cardiovascular response during emergence in patients undergoing total laparoscopic hysterectomy

Abstract: Objective: To investigate the optimal dose of dexmedetomidine for attenuating the haemodynamic response during emergence from anaesthesia. Methods: Patients undergoing laparoscopic total hysterectomy were randomly allocated to receive 0.9% normal saline (control group) or dexmedetomidine (0.5 mg/kg, 0.75 mg/kg or 1.0 mg/kg 30 min) before extubation. Heart rate, systolic and diastolic arterial pressure and extubation time were measured before drug administration, immediately after the end of drug administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…However, we found that the incidences of bradycardia in the groups dexmedetomidine 0.4ug/kg, 0.6ug/kg and 0.8ug/kg were 10.00%, 13.33% and 16.67% respectively, indicating that the incidence of bradycardia increased with the increase of dexmedetomidine dose. Seo KH et al also found that the incidences of bradycardia at 0.75ug/kg and 1ug/kg increased compared with that at 0.5ug/kg [15] , which was consistent with our nding. The occurrence of bradycardia is related to the inhibition of atrioventricular node and sinoatrial node function, reduction of catecholamine content in the blood and excitation of vagus nerve by dexmedetomidine [12,16] .…”
Section: Discussionsupporting
confidence: 92%
“…However, we found that the incidences of bradycardia in the groups dexmedetomidine 0.4ug/kg, 0.6ug/kg and 0.8ug/kg were 10.00%, 13.33% and 16.67% respectively, indicating that the incidence of bradycardia increased with the increase of dexmedetomidine dose. Seo KH et al also found that the incidences of bradycardia at 0.75ug/kg and 1ug/kg increased compared with that at 0.5ug/kg [15] , which was consistent with our nding. The occurrence of bradycardia is related to the inhibition of atrioventricular node and sinoatrial node function, reduction of catecholamine content in the blood and excitation of vagus nerve by dexmedetomidine [12,16] .…”
Section: Discussionsupporting
confidence: 92%
“…8 Eight RCTs had >2 groups. 8,9,19,21,27–29,31 A total of 899 patients undergone laparoscopic surgeries were included in the meta-analysis. A total of 451 patients were administrated with DEX and 448 were with placebo or no treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Six trials 9,20,21,23,25,29 including 360 patients compared extubation time in patients treated with DEX or control. No significance was observed between 2 groups (MD = 0.70, 95% CI: −0.89 to −2.28, P  = 0.39, I 2  = 98%) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Intravenous administration of oxycodone can help modifying hemodynamic response to laryngoscopy and intubation during induction phase and can be an adjuvant drug to inhalation agents during maintenance period of general anesthesia. The optimal dose of fentanyl [3] or dexmedetomidine [8] for attenuating the hemodynamic changes during induction was investigated. However, the recommendations for the appropriate dosage of oxycodone, especially for intubation, are insufficient.…”
Section: Introductionmentioning
confidence: 99%